FENOMENA MEME HADIS CELANA CINGKRANG DALAM MEDIA SOSIAL - Miski Miski (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2017)
This written is aimed to study more about popular culture, espesially in relation to meme phenomenon of shorten-long pants hadith (meme hadis celana cingkrang) spread around social media. From paradigm that this phenomenon is not only about creativity and wasn’t born at an empty space in social world, so the question is what behind this phenomenon is? To answer this question, this study is using constructivism paradigm with discourse analysis framework, all of the data are documentation and analyzed by using content analysis method, that is by means of exploration process, selection and classification so interpretation. This study shows that as religious phenomenon, at least there are two main problems behind meme phenomenon of shorten-long pants hadith. The first, it is an efforts to strengthen the religiousness identity of textual group among ideological contestation. The second, it is a form of their retaliation for the various shapes of resistance the common society does. This finding also strengthen the existence and textual group power relation along with political condition which they may be more free and having a notion and expressing the religious practice which is fully supported by the easiness of literature accessing, both directly or by relevant website.